Komunikasi Keluarga bagi Perempuan Dewasa Fatherless dalam Memilih Pasangan Hidup di Kota Bandung - Arnest Chania Putri; Safutra Rantona; Yuni Dahlia Yosepha Mogot (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
he fatherless phenomenon in Bandung City affects family communication patterns and influences how adult women determine partner criteria. This study aims to examine the conversation and conformity orientations in the family communication of fatherless adult women when choosing a life partner. The research employed a qualitative case study approach using purposive sampling, involving four key informants and eight supporting informants. The findings indicate that conversation orientation is more focused on the mother, but is limited by feelings of awkwardness and inequality in speaking positions, reducing openness in discussing life values. The conformity orientation, centered on the mother as the dominant figure, does not always reach the child due to emotional differences and the indirect delivery of expectations, which create emotional distance and tension. The mother assumes a dual role as the source of values, moral guidance, and understanding of family life; however, communication tends to be one-sided and less balanced. The study recommends that individuals who have experienced the loss of a father figure develop self-awareness regarding the influence of past experiences in partner selection, understand the relationship values they believe in, and foster healthy communication to build more stable and meaningful relationships. In addition, the study highlights the importance of creating safe spaces for dialogue within the family, so that openness and equality in communication can emerge. Strengthening social support systems, including peer and community support, can also complement family communication, thereby helping fatherless adult women establish healthier relationship choices in the future.